Empathy Study - Kondo, Makiko; Nikku, Bala (IntechOpen, 2020)
Empathy, as it relates to behavioral counseling, is the ability of the counselor to get into the client's phenomenological world and experience it as if it is one's own while putting aside one's own feelings and accepting the client's thoughts and feelings unconditionally. Empathy is indispensable not only for forming good relationships but also for healing hurt persons. Especially now, empathy is the essence of care. This book contains chapters that cover transpersonal caring, learning to be empathic in social school, autism and psychopathy, emotional labor, and critical thinking in social work training from a variety of different perspectives.